6 S.A. ARMOURED DIVISION IN ITALY - Jacobs, F.J.; Bouch, R.J. (Scientia militaria : South African journal of military studies, 2012)
WINTER '1944 - 1945The period 20 - 23 October was the climax of the offensive, not only on 6 SA Armoured Divisional sector, but on the front of the whole Fifth Army. II US Corps had been attacking with great determination east of Route 65, and on 23 October 34 Division captured Mt Belmonte, only 9 miles from the centre of Bologna. "This was II Corps finest effort, and it was destined to be their last. The Germans, now under the supreme command of Gen Von Vietinghoff for Kesselring had been seriously wounded in an air attack, took desperate measures to ensure the defence of Bologna. From the Eighth Army front Von Vietinghoff brought over 90 Panzer Grenadiers and 1 Parachute Division, both famous for the defence of Cassino. II Corps was exhausted and these strong enemy reinforcements turned the scale. No further advance North-West could be made and on 27 October, Fifth Army went over to the defensive. To be robbed of a decisive success after so long and sanguinary a struggle was the more bitter in that the price already paid would have been heavy even if paid for victory.'"